Impacts of Citric Acid and Malic Acid on Fermentation Quality and Bacterial Community of Cassava Foliage Silage - Li, Mao; Zhang, Lidong; Zhang, Qing; Zi, Xuejuan; Lv, Renlong; Tang, Jun; Zhou, Hanlin (Frontiers in Microbiology, 2020)
The microbiota and fermentation quality of cassava foliage (CF) ensiled in the absence of additive (CK), or in the presence of citric acid (CA), malic acid (MA), and their combination with a Lactobacillus plantarum strain (CAL and MAL) were investigated. These additives reduced (P<0.05) the pH, butyric acid and ammonia-N contents, but increased (P<0.05) the lactic acid content, and CAL and MAL showed the similar remarkable effects. Paenibacillus (mean 27.81%) and Bacillus (mean 16.04%) were predominant strains in CF silage. The addition of CA or MAL increased the abundance of Paenibacillus (25.81% to 52.28% and 47.97%), and the addition of MA increased the abundance of Bacillus (15.76% to 32.48%) compared with the CK group. Moreover, CAL and MAL increased the abundances of the potential desirable bacteria Cellulosimicrobium (CAL 0 to 12.73%), Hyphomicrobium (0 to 7.90% and 8.94%) and Oceanobacillus (0 to 8.37% and 3.08%) compared with the CK group. These findings suggested that CA and MA could enhance the silage quality of CF, and their combinations with Lactobacillus plantarum were more effective.